1986
DOI: 10.1136/bmj.292.6529.1165
|View full text |Cite
|
Sign up to set email alerts
|

Impact of maternal postnatal depression on cognitive development of young children.

Abstract: Ninety four women and their first born children took part in a longitudinal study of maternal mental health during pregnancy and after delivery. The children's cognitive functioning was assessed at age 4 using the McCarthy scales, without knowledge of the mothers' psychiatric history or current health. As expected girls performed slightly better than boys and children from middle class and professional families did better than children from working class homes, as did children whose mothers had achieved at lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
289
3
6

Year Published

1991
1991
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 530 publications
(306 citation statements)
references
References 20 publications
8
289
3
6
Order By: Relevance
“…In a study by Sharp et al (23), only boys showed a decrease on standardized tests of intellectual attainment (mainly on indexes of abstract intelligence, reasoning about opposites and analogies) and the "draw-achild" task. Other aspects of cognitive development, such as cognitive-linguistic functioning (24), have also been shown to be negatively affected, and there were also deficits on the perceptual and performance scale (25). Outcome effects were independent of birth order, maternal education, family income, marital status and social support.…”
Section: Cognitive Developmentmentioning
confidence: 78%
“…In a study by Sharp et al (23), only boys showed a decrease on standardized tests of intellectual attainment (mainly on indexes of abstract intelligence, reasoning about opposites and analogies) and the "draw-achild" task. Other aspects of cognitive development, such as cognitive-linguistic functioning (24), have also been shown to be negatively affected, and there were also deficits on the perceptual and performance scale (25). Outcome effects were independent of birth order, maternal education, family income, marital status and social support.…”
Section: Cognitive Developmentmentioning
confidence: 78%
“…The effects of this have been shown to persist until the infant is at least 18 months of age [4]. Several studies have also shown that children of women with postnatal depression tend to do less well later, both in terms of their behaviour and their intelligence [5,6]. This may well be, at least in part, because their mothers have not been able to give them the necessary stimulation and affection in the early months.…”
mentioning
confidence: 83%
“…Emotional effects include increased negativity and fearfulness (Pauli-Pott et al, 2004) and behavior problems (Beck, 1999) as well as more insecure attachments (Cicchetti et al, 1998). Cognitive effects on children experiencing maternal depression have been documented across childhood (Brennan et al 2000;Cogill et al, 1986;NICHD Early Child Care Research Network 1999). Physiological consequences for children of depressed mothers include less weight gain in the first 2 yr of life (Hendrick 2003;O'Brien et al, 2004), elevated cortisol and norepinephrine, and lower dopamine levels (Diego et al 2004;Halligan et al, 2004).…”
Section: Introductionmentioning
confidence: 99%